Understanding value change. (1st June 2022) - van de Poel, Ibo
Abstract : The possibility of value change has implications for how to responsibly develop and deploy new technologies. If values can, and do, change after technologies have been developed and designed, this would seem to have major ramifications for approaches such as value-sensitive design and responsible innovation. This contribution explores descriptive as well as normative accounts of value change. It suggests three methodological principles that descriptive accounts of value change should meet. Normative accounts are relatively independent of descriptive accounts and raise the important question of whether normative or moral values themselves can also change. Through the example of the birth control pill and its (alleged) effect on sexual morality, the article illustrates what descriptive and normative accounts might look like in a concrete case. It closes with a discussion of implications for responsibly developing new technologies and draws some conclusions for more theoretical work on value change.